Postglacial recolonization and Holocene diversification of Crocidura suaveolens (Mammalia, Soricidae) on the north-western fringe of the European continent. (15th June 2018) - Rofes, Juan; Cucchi, Thomas; Hanot, Pauline; Herman, Jeremy; Stephan, Pierre; Cersoy, Sophie; Horáček, Ivan; Kerr, Elizabeth; Allberry, Kate; Valenzuela, Silvia; Zazzo, Antoine; Cornette, Raphaël; et al.
Abstract: Phenotypic variation was characterized in 187 modern and archaeological specimens of the lesser white-toothed shrew ( Crocidura suaveolens ), obtained from both insular and continental European locations. Geometric morphometric methods were used to quantify variation in size and shape of the mandible. The phenotypic distance between populations, and the influence of several eco-geographical factors on the size and shape of the mandible in island populations, were assessed. Based on mandible shape divergence, the populations of C. suaveolens were clustered into continental, insular Atlantic and insular Mediterranean groups. Archaeological specimens from Molène Island, more than 3400 years old, display a mandible shape signal closer to that of the continental population than those of modern island populations. Conversely, the continental shape signals of the modern populations from Höedic and Sark suggest that these are relatively recent anthropogenic introductions. The populations of C. suaveolens from both the Atlantic and Mediterranean islands (except for Rouzic and Cyprus) show a significant increase in mandible size, compared to those from continental Europe. Significant phenotypic differences support the indigenous condition of C. suaveolens on most of the Atlantic islands, suggesting that the species arrived there before the separation of the Scilly Isles and Ushant from the continent due to the post-glacial rise in sea level. This provides an ante quem for its colonization of the north-western fringe of continental Europe, notwithstanding its absence from the region in the present day. Highlights: Mandible shape of C. suaveolens demonstrates geographical clustering within Europe. Archaeological specimens from Molène Island display a continental signal. Shape signals of Höedic and Sark islands suggest recent anthropogenic introductions. Increase in size preceded changes in shape in Molène, Hoëdic and Sark. Phenotype differences support native condition of C. suaveolens on Atlantic islands.